PENINGKATAN MENULIS SURAT PRIBADI MELALUI MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) DI KELAS X SMA SWASTA NURUL ILMI PADANGSIDEMPUAN TAHUN PELAJARAN 2025-2026 - Fita Delia Gultom; Elnila Caniago; Erni Rawati Sibuea (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
This research was conducted at Nurul Ilmi Padangsidempuan Private High School in the 2025-2026 academic year using the PTK research method with a sample of 30 students. The results showed an improvement in students' drama script writing through the specified Minimum Competency (KKM). The results obtained in the pre-cycle, based on the DKN (National Skills) assessment, were still low, with 14% still failing to complete the KKM. Then, the first cycle of action was carried out, with the number of students passing the KKM still remaining at 50%. While the second cycle experienced a change, with the number of students passing the KKM reaching 90%, this indicates an increase that has exceeded the target of 80%.